2010
DOI: 10.2215/cjn.09421209
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Trial of Spironolactone on Carotid Intima-Media Thickness in Nondiabetic Hemodialysis Patients

Abstract: Background and objectives: Hemodialysis patients (HD) display high rates of cardiac diseases and mortality. In chronic kidney disease, vascular injury leads to coronary artery disease, heart failure, and stroke. Carotid intima-media thickness (CIMT) measurements are currently widely used in randomized controlled trials (RCTs) to study the efficacy of interventions. An RCT was designed for the assessment of the safety and effectiveness of spironolactone to inhibit the progression of CIMT in HD patients as a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 35 publications
1
83
2
2
Order By: Relevance
“…After full-text screening, one article was excluded as no data of serum potassium for the control group was provided. 21 Eleven studies were reported in this systematic review, among which five studies were RCTs [22][23][24][25][26] and six were non-randomized studies [27][28][29][30][31][32] ( Figure 1). …”
Section: Search Resultsmentioning
confidence: 99%
“…After full-text screening, one article was excluded as no data of serum potassium for the control group was provided. 21 Eleven studies were reported in this systematic review, among which five studies were RCTs [22][23][24][25][26] and six were non-randomized studies [27][28][29][30][31][32] ( Figure 1). …”
Section: Search Resultsmentioning
confidence: 99%
“…In human hypertensive patients, MRA improved flow-mediated dilation, a mechanism contributing to vascular tone in hypertension (Fujimura et al, 2012). In patients with end-stage renal disease (ESRD), MRA also had favorable effects on intima-media remodeling (Vukusich et al, 2010). Of note, two studies reported a nondiuretic effect on blood pressure in patients with ESRD treated with spironolactone or eplerenone (Gross et al, 2005;Shavit et al, 2012).…”
Section: Mineralocorticoid Receptor and Vascular Diseasesmentioning
confidence: 99%
“…Spironolactone thrice weekly post-dialysis was shown to significantly reduce the progression of CIMT after two years as compared with placebo. 42 …”
Section: Cimtmentioning
confidence: 99%